Photo-rechargeable zinc-ion batteries. Issue 8 (30th June 2020) - Boruah, Buddha Deka; Mathieson, Angus; Wen, Bo; Feldmann, Sascha; Dose, Wesley M.; De Volder, Michael
Abstract : This paper presents a zinc-ion battery that can be recharged directly by light without the need for a solar cell, which offers a new approach to balancing the unpredictable energy surpluses and deficits associated with solar energy. Abstract : Batteries that can be directly recharged by light would offer a new approach to balancing the unpredictable energy surpluses and deficits associated with solar energy. Here, we present a new aqueous zinc-ion battery (photo-ZIB) that can directly harvest sunlight to recharge without the need for external solar cells. The light charging process is driven by photo-active cathodes consisting of a mixture of vanadium oxide (V2 O5 ) nanofibers, poly(3-hexylthiophene-2, 5-diyl) and reduced graphene oxide, which provide the desired charge separation and storage mechanism. This process is studied using photodetectors, transient absorption spectroscopy and electrochemical analysis in dark and light conditions. The V2 O5 cathodes have gravimetric capacities of ∼190 mA h g −1 and ∼370 mA h g −1 in dark and illuminated conditions respectively and photo-conversion efficiencies of ∼1.2%. Finally, we demonstrate a fully functional photo-ZIB with a ∼64 cm 2 optical window in pouch cell format.